Improving Shareholder Value through Corporate Governance Mechanism in Malaysian Listed Companies - Ibrahim, Mohammed Yussoff; Ahmad, Ayoib Che; Khan, Muhammad Anees (International Journal of Economics and Financial Issues, 2016)
This paper proposes to investigate the postulations of renowned agency theory and shareholder value (SHV) in relation to Corporate Governance (CG) attributes. Shareholder value is of a great concern to the shareholders of firms. Shareholder value have been investigated by numerous studies of corporate governance but with inconsistent empirical evidence. This study will focus on investigating the impact of CG attributes on Shareholder value measured by Tobin’s Q or return on both equity and assets. The paper conceptualized four attributes (Separate leadership, proportion of Independent director, independent chairman, independence of nomination committee) from Corporate Governance mechanism in relation to shareholder value in companies listed on BURSA Malaysia. This is a conceptual paper which proposes to investigate the relationship between shareholder value and separate leadership, shareholder value and proportion of independent director, shareholder value and independent chairman, shareholder value and independence of nomination committee in the context of Malaysia. The proposed study has value for Malaysian government, policy makers, corporate boards, stock exchange and shareholders by highlighting the distinct impact on shareholder value and its relation with separate leadership, proportion of independent director, independent chairman, and independence of nomination committee. Keywords: Shareholder Value, Corporate Governance Mechanism JEL Classification: G34